Pengamanan Data Nilai Mahasiswa Menggunakan Algoritma Caesar Chiper dan RSA Berbasis Web - Putri, Nurhaliza Aulia; Hesti, Emilia; Aryanti, Aryanti (Prahasta Publisher, 2024)
The development of technology and information in the current digital era has profoundly influenced human activities, particularly in the field of education. In this highly sophisticated age, all academic activities utilize technology with appropriate security measures to safeguard confidential data. Various security techniques, including cryptographic methods, have been developed to ensure data confidentiality. The methods employed for data security utilize the Caesar Cipher and RSA algorithms. In applying these algorithms, several stages are involved: the original data (plaintext) is encrypted using the Caesar Cipher algorithm by determining a shift value K to displace each character. Subsequently, the data is encrypted using the RSA algorithm by determining two distinct keys p and q. The RSA algorithm involves two keys, namely the public and private keys. The public key is used for encryption, while the private key is used for decryption processes. This research focuses on securing student grade data from unauthorized access and falsification using the Caesar Cipher and RSA methods. Test results indicate that both the Caesar Cipher and RSA encryption processes successfully transform plaintext into ciphertext that cannot be directly read without appropriate decryption processes.